2020
DOI: 10.1186/s40510-020-00343-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 405-, 532-, 650-, and 940-nm wavelengths of low-level laser therapies on orthodontic tooth movement in rats

Abstract: Background Investigating the effects of 405-nm, 532-nm, 650-nm, and 950-nm wavelengths of LLLTs (low-level laser therapies) on the orthodontic tooth movement in rats by using histological and immunohistochemical methods. Forty-five Wistar albino rats were randomly divided into 5 groups: control group (positive control: the left maxillary 1st molar side; negative control: the right maxillary 1st molar side), 405 nm LLLT group (Realpoo), 532 nm LLLT group (Realpoo), 650 nm LLLT group (Realpoo), and 940 nm LLLT g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Studies have shown that near-infrared light can penetrate biological tissues more effectively than visible light. 18,19 Existing interpretations suggest that light energy emitted by laser therapy devices is predominantly absorbed within the first 10 mm of biological tissue. This finding aligns with previous research indicating that laser light can penetrate several millimeters into biological tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that near-infrared light can penetrate biological tissues more effectively than visible light. 18,19 Existing interpretations suggest that light energy emitted by laser therapy devices is predominantly absorbed within the first 10 mm of biological tissue. This finding aligns with previous research indicating that laser light can penetrate several millimeters into biological tissues.…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it is not difficult to see that there are different light parameters in different articles, especially wavelengths (Table 1). Keklikci et al [42] found that 650 nm and 940 nm light presented better osteogenic ability in the area between the roots than 405 nm and 532 nm light, and 405 nm light formed the least bone, which could be attributed to increased intracellular oxygen radicals [43]. Furthermore, 650 nm light could decrease osteoclastogenesis by reducing intracellular oxygen radicals [43].…”
Section: The Efficacy Of Pbm Therapy On Otm In Cell and Animal Experi...mentioning
confidence: 99%
“…Despite the advantages, the application of PBM in orthodontics is met with several challenges. The absence of standardized treatment protocols is a primary limitation, introducing variability in treatment parameters and outcomes [28,[42][43][44][45][46]. This variability is compounded by individual differences in response to PBM, which can hinder the development of universal treatment guidelines [28].…”
Section: Limitations Of Photobiomodulation In Orthodontic Treatmentmentioning
confidence: 99%
“…Moreover, the effective utilization of PBM devices requires specific clinician training to prevent potential misuse or excessive use, which could lead to tissue damage. Another significant barrier to the widespread adoption of PBM is the cost of laser equipment, which, along with the need for intensive safety training, may limit accessibility for some practices and patients [24,25,[38][39][40][41][42][43][44][45][46].…”
Section: Limitations Of Photobiomodulation In Orthodontic Treatmentmentioning
confidence: 99%